High prevalence of multiple paternity in the invasive crayfish species, Procambarus clarkii - Gen Hua Yue, Jia Le Li, Chun Ming Wang, Jun Hong Xia, Gen Lin Wang, Jian Bing Feng (International Journal of Biological Sciences, 2010)
Reproductive strategy is a central feature of the ecology of invasive species as it determines the potential for population increase and range expansion. The red swamp crayfish, Procambarus clarkii, has invaded many countries and caused serious problems in freshwater ecosystems. However, little is known about the effects of environmental conditions on crayfish paternity and offspring traits in the wild. We studied these reproductive characteristics of P. clarkii in wild populations from two different habitats (ponds and ditches) in three locations with different environmental conditions in China. Genotyping of 1,436 offspring and 30 mothers of 30 broods was conducted by using four microsatellites. An analysis of genotyping results revealed that gravid females were the exclusive mother of the progeny they tended. Twenty-nine of 30 mothers had mated with multiple (2-4) males, each of which contributed differently to the number of offspring in a brood. The average number of fathers per brood and the number of offspring per brood were similar (P > 0.05) among six sampling sites, indicating that in P. clarkii multiple paternity and offspring number per brood are independent of environmental conditions studied. Indirect benefits from increasing the genetic diversity of broods, male and sperm competition, and cryptic female choice are a possible explanation for the high level multiple paternity and different contribution of fathers to offspring in this species.